Engineering behavior of soil treated by chemical and electrokinetics - Lee, Shyue Leong (Universiti Malaysia Sarawak (UNIMAS), 2013)
Soft soil has the characteristics of high compressibility, low shear strength and low permeability. Research on soft soil stabilization was conducted to determine the strength development of treated soil. Chemical stabilization with lime and electrokinetic stabilization were used. Different lime contents were added to the soil for lime stabilization and electrokinetics-lime stabilization and the samples were tested after the curing period by using vane shear test equipment. Comparison of strength gained for both lime stabilization and electrokinetics-lime stabilization was conducted including the determination of optimum lime content required. The reason behind the strength gained for the treated soil is due to the pozzonalic reaction to produce calcium silicate hydrate (CSH) and calcium aluminium hydrate (CAH), which bind with the soil particles and increase the strength of the soil. The difference between lime stabilization and electrokinetics-lime stabilization is direct current is applied on the electrokinetics-lime stabilization for 1 hr at the voltage gradient of 34.96 V/m. The strength of lime stabilized soil increased by 16.43% for 7.5% to 12.5 % lime content. However, the strength of the elctrokinetics-lime stabilized soil decreased for 25.61% with increase in lime content from 7.5% to 12.5%. Hence, it can be concluded that lime stabilization is more effective than electrokineticslime stabilization in this research.